Giant cell arteritis: the importance of immediate and appropriate diagnosis and treatment for better prognosis - Pacella F (Dove Medical Press, 2012)
Fernanda Pacella,1 Francesco Mazzeo,1 Dario Giorgi,1 Francesco Cerutti,1 David Impallara,1 Giovanni Cuozzo,1 Maurizio Soldini,2 Elena Pacella11Department of Ophthalmology, 2Service Detachment of Internal Medicine and Cardiology, Department of Ophthalmology, Sapienza University, Rome, ItalyAbstract: This article describes the case of a 68-year-old patient suffering from giant cell arteritis (also known as Horton’s arteritis or temporal arteritis). The patient came to our attention due to a large and sudden visual loss caused by the occlusion of major retinal arteries. The patient had neuralgic pain in the face. The next day, for a thorough examination, the patient went to the day hospital with a further worsening of the visual loss which required immediate admission to the ophthalmological ward for hospitalization lasting 10 days. During the observation period it was difficult to make an instant diagnosis due to the absence of clinical signs or diagnostic tests for Horton’s arteritis. Only after the third day of hospitalization, when corticosteroid therapy was undertaken following the appearance of significant systemic symptoms, did the patient begin to show a gradual improvement in overall clinical status. The case highlights the difficulty in making a rapid diagnosis of giant cell arteritis and the efficacy of early steroid therapy in this vascular autoimmune disease that otherwise may result in irreversible functional and debilitating systemic damage.Keywords: temporal arteritis, Horton’s arteritis, corticosteroid